Penyelesaian Permasalahan Keluarga secara Mediasi Non Litigasi Perspektif Hukum Islam dan Hukum Positif - Selinah, Selinah; Dalimunthe, Paisal Ahmad; Ismail, Hidayatullah (Hamalatul Qur'an : Jurnal Ilmu Ilmu Alqur'an, 2024)
The implementation of non-litigation mediation is very important in the community, considering that the number of family dispute cases brought to religious courts is increasing every day. The implementation of non-litigation mediation in this law results in practice, people in various regions tend to resolve disputes through mediation in accordance with the customs and culture that prevail in their respective environments. This research is a library research. Literature research is a study method that aims to collect information and data by utilizing various material sources available in the library. The results of the study show that from the perspective of Islamic law, mediation is considered an effective tool to resolve disputes in a faster and lower cost way. This process can also help the parties reach a better agreement and fulfill a sense of justice (Shaifullah). Out-of-court consultation refers to Surah An-Nisa verse 35.  Meanwhile, in positive law, conflict resolution methods are known as negotiation, litigation, mediation, and arbitration.